INFLUENCE OF EPICHLOROHYDRIN, THE EXTRACT OF ECHINACEA PURPUREA AND THIOTRIAZOLINE ON THE SUBMUCOSA OF THE PYLORIC PART OF THE STOMACH OF RATS - Smirnov А.S.; Mirzebasov, M.A. (World of Medicine and Biology, 2016)
In experiments on white rats studied the nature of the changes in the submucosa of the pyloric part of the stomach after two-month inhalation exposure of epichlorohydrin, administration of the extract of Echinacea purpurea and thiotriazoline. Epichlorohydrin causes an increase in the thickness of the submucosa of the pyloric part of the stomach of rats, which is observed for thirty days after the end of its inhalation. Introduction of Echinacea purpurea extract increases the thickness of the submucosa in rats which are not treated with epichlorohydrin, and decreases the thickness of this structure in rats which are treated with epichlorohydrin. Extract of Echinacea purpurea and thiotriazoline reduces the severity of increasing the thickness of the submucosa caused by epichlorohydrin. Thiotriazoline also reduces the duration of this effect of epichlorohydrin.